Policy of the Financial Services Authority in Consumer Protection - Widijantoro, Johanes; Wijaya, Nikolaus Budi A. (International Journal of Economics and Financial Issues, 2018)
Financial Services Authority (FSA) is the independent body that have responsible in oversight of Financial Industries in Indonesia, both Banking and non-Banking. One of the main objective in establishing of FSA is to provide consumer protection. It was broadly known that consumers of financial services were frequently damaged because of various unfair trade practices conducted by financial service providers, their low level of financial literacy, and the weakness of consumer protection policy. This article examines development of consumer protection policies released by FSA since its establishment. A concisely review of the consumer protection policy before the establishment of FSA will also be conducted to see how far the policy of consumer protection of financial services existed at that time. By using some relevant aspects in consumer protection of financial services, policies of FSA in protecting consumer will be analyzed to describe its progress as well as its weakness and challenge. Keywords: Financial Service Authority, consumer protection, financial services. JEL Classifications: E610, G2